Epidemiology, Biology, Treatment, and Prevention of Ductal Carcinoma In Situ (DCIS). Issue 4 (27th December 2018) - Punglia, Rinaa S; Bifolck, Kaitlyn; Golshan, Mehra; Lehman, Constance; Collins, Laura; Polyak, Kornelia; Mittendorf, Elizabeth; Garber, Judy; Hwang, Shelley E; Schnitt, Stuart J; Partridge, Ann H; King, Tari A
Abstract: Ductal carcinoma in situ (DCIS) is a highly heterogeneous disease. It presents in a variety of ways and may or may not progress to invasive cancer, which poses challenges for both diagnosis and treatment. On May 15, 2017, the Dana-Farber/Harvard Cancer Center hosted a retreat for over 80 breast specialists including medical oncologists, surgical oncologists, radiation oncologists, radiologists, pathologists, physician assistants, nurses, nurse practitioners, researchers, and patient advocates to discuss the state of the science, treatment challenges, and key questions relating to DCIS. Speakers and attendees were encouraged to explore opportunities for future collaboration and research to improve our understanding and clinical management of this disease. Participants were from Dana-Farber Cancer Institute, Brigham and Women's Hospital, Massachusetts General Hospital, Beth Israel Deaconess Medical Center, Duke University Medical Center, and MD Anderson Cancer Center. The discussion focused on three main themes: epidemiology, detection, and pathology; state of the science including the biology of DCIS and potential novel treatment approaches; and risk perceptions, communication, and decision-making. Here we summarize the proceedings from this event.